تاثير تمرينات القوة بأوضاع متنوعه على الرجلين والذراع الرامية والسرعه في مرحلتي الدوران و رمي القرص للشباب - الخفاجي, محمد عبادي عبد; الواحد, بشائر هاشم عبد (Sulaimani Journal for Humanities, 2018)
The goal of the study preparation exercises to develop strength with various preparatory conditions to demonstrate its impact on the strength of the muscles of the legs and arm to disk and develop speed in placing the throw and throw (the arms and legs and torso) sample intentional way search players discus 10 clubs and players have been divided into two random way amounted to each group (5) players per group, the researchers then conducted a test to measure the instantaneous power of the arm towards the instantaneous power measurement and test of driving men to use force measurement platform, Put the platform in the middle of a circle throw so that the player who put the driving man (right) during the performance of the method of rotation, to extract the instantaneous force amounts that swapping a second performance of the discus. As well as filming during sample performance through a security camera filming gusting 300 p/w. Training methodology was applied to a sample search data measured force of arms and legs for eight weeks and three training units per week and then post training testing and comparison search variables, and finally it appeared clear to influence search results to improve the strength and speed of these parts and improve disk starting variables during the throw.